2015
DOI: 10.1016/j.jneumeth.2014.12.016
|View full text |Cite
|
Sign up to set email alerts
|

SWDreader: A wavelet-based algorithm using spectral phase to characterize spike-wave morphological variation in genetic models of absence epilepsy

Abstract: Background Spike-wave discharges (SWD) found in neuroelectrical recordings are pathognomonic to absence epilepsy. The characteristic spike-wave morphology of the spike-wave complex (SWC) constituents of SWDs can be mathematically described by a subset of possible spectral power and phase values. Morlet wavelet transform (MWT) generates time-frequency representations well-suited to identifying this SWC-associated subset. New method MWT decompositions of SWDs reveal spectral power concentrated at harmonic freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 44 publications
(50 reference statements)
2
24
0
Order By: Relevance
“…Our data show that events along the spectrum of the SVM score (and thus SWD confidence) show temporal and proportional correlations with abrupt changes in EEG power bands. 16 We also identified SWD-like events in wild-type mice, consistent with the hypothesis that SWD events represent a corruption of otherwise normal brain processes. Qualitatively similar temporal patterns were observed in all of the γ2R43Q animals analyzed in this study (data not shown).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Our data show that events along the spectrum of the SVM score (and thus SWD confidence) show temporal and proportional correlations with abrupt changes in EEG power bands. 16 We also identified SWD-like events in wild-type mice, consistent with the hypothesis that SWD events represent a corruption of otherwise normal brain processes. Qualitatively similar temporal patterns were observed in all of the γ2R43Q animals analyzed in this study (data not shown).…”
Section: Discussionsupporting
confidence: 86%
“…The algorithm was trained using a dataset with 2500 putative events and labels (SWD or nonSWD) from 4 expert human scorers, using fivefold internal cross validation, and tested against the performance of 2 human scorers (S1 and S4) on multiple, unannotated (no computer information), and out-of-training data records. Although other groups have developed algorithms for the detection of SWDs, [16][17][18][19] to the best of our knowledge, no other group has designed an algorithm to mirror human confidence in scoring. Instead, it drew fuzzy, tightly interleaved boundaries similar to those of human scorers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A SWD reader for mice was recently described (Richard et al, 2015). The cortical ECoG's(3 bipolar differential and 3 referenced recordings) of mice carrying the Gria4, Gabrg2, or Scn8a mutations showing SWDs were analysed with a Morlet wavelet transform and both spectral power and spectral phase values were calculated, the latter in order to quantify morphological variants of the SWDs, a feature that has not been quantified before.…”
Section: Detection Of Swds: Off Line Methodsmentioning
confidence: 99%